CHANGING TREND OF EMPLOYEE ENGAGEMENT PRACTICES : A STUDY - Rakesh. R (REVIEW OF SOCIAL SCIENCES, 2014)
Employee Engagement is defined as the extent to which employees are motivated to contribute to organizational success. It is the level of commitment and involvement an employee has towards their organization and its values. An awesome workplace is one where people want to join, they want to perform well, and they want to tell everyone just how awesome their work is. As the ratio of people who fit this description increases, so too does the degree of awesomeness. Awesomeness builds brands & sustains success. Research has long shown that engaged employees lead to more successful companies. Engaged employees are more productive and deliver higher customer service, which results in greater financial success for their employers. This is perhaps the reason that for several years now, ‘employee engagement’ has been a hot topic in corporate circles. It’s a buzz phrase that has captured the attention of workplace observers, HR managers as well as the top management. This paper focuses on the relation between employee engagement & high performing culture &what should company do to make the employees engaged. It also looks at the changing trends prevailing in the arena of employee engagement with the changing economy & scenario.